Rancang Bangun Alat Ukur Gaya Pada Wind Tunnel Menggunakan Sensor Load Cell - Denny Dermawan (Retii, 2020)
In the Aerodynamics laboratory at the Adisutjipto College of Technology, the wind tunnel mass measuring instrument only uses an ordinary digital scale. So to facilitate reading in the wind tunnel, a tools is built using a load cell sensor and with digital readings that have been converted from mass to force. This data reading system is connected to an LCD as a display in monitoring the resulting speed changes. By using the data collection method, and also after performing tool calibration and testing with ordinary digital scales, results were found by using the NACA 4412 airfoil test object and by testing where there were different angle of attack. From the results, it can be concluded that measurements made at different angle of attack have different values ​​even with the same wind speed. This happens because there are several factors, and the error factor that the wind tunnel has in the Aerodynamics Laboratory of the Adisutjipto College of Technology reaches an average of 3.6%.